2011
DOI: 10.1561/100.00010041
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effect of Media-Driven Political Interest on Political Attitudes and Behavior

Abstract: This article considers the hypothesis that media-driven political interest shapes party identification, the timing of vote decisions, and electoral participation. To estimate the effect of media-driven political interest, we make a key distinction between political interest as a lifetime political orientation and political interest that rises and falls with the occurrence of noteworthy political events. We then exploit the shared media markets in Switzerland and its neighboring countries to overcome the otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that negative framing of refugees influences mass attitudes: support for redistribution and integration diminishes (Avdagic and Savage 2020). We also refer to studies of political communication that demonstrate that consistent messaging has a non-trivial effect on party support and electoral outcomes (DellaVigna et al 2014; Adena et al 2015; Butler and De La O 2011; Crabtree and Kern 2018).…”
Section: Importance Of Foreign Political Communication In the Electionsmentioning
confidence: 99%
“…It has been demonstrated that negative framing of refugees influences mass attitudes: support for redistribution and integration diminishes (Avdagic and Savage 2020). We also refer to studies of political communication that demonstrate that consistent messaging has a non-trivial effect on party support and electoral outcomes (DellaVigna et al 2014; Adena et al 2015; Butler and De La O 2011; Crabtree and Kern 2018).…”
Section: Importance Of Foreign Political Communication In the Electionsmentioning
confidence: 99%
“…Previous research shows that cross-national media effects exist: Exposure to German television increased voter turnout in Switzerland (Butler and De La O 2011); Serbian radio induced nationalist behaviour among living in the bordering regions Croatians (DellaVigna et al 2014), Western television increased public support for the communist regime in East German, and China (Kern and Hainmueller 2009; Huang and Yeh 2017), Russian television polarized Russian and Ukrainian speaking public in Ukraine over presidential and parliamentary elections (Peisakhin and Rozenas 2018). The effects of biased media in the context of foreign politics however remains unclear.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…One body of literature argues that political interest is highly stable in adulthood (Prior 2010), rooted in family socialization (Neundorf, Smets and García-Albacete 2013), psychological dispositions (David 2009;Gerber et al 2011a) and encoded into our genes (Dawes et al 2014;Weinschenk and Dawes 2017). A second body of literature argues that political interest is shaped by features of the environment, such as election campaigns (Butler and De La O 2010), historical and economic events (Prior 2002;van Deth and Elff 2004), and mass media (Sørensen 2019).…”
mentioning
confidence: 99%